Software and network engineering - Lee, Roger (Studies in Computational Intelligence, 2012)
The series "Studies in Computational Intelligence" (SCI) publishes new developments and advances in the various areas of computational intelligence - quickly and with a high quality. The intent is to cover the theory, applications, and design methods of computational intelligence, as embedded in the fields of engineering, computer science, physics and life science, as well as the methodologies behind them. The series contains monographs, lecture notes and edited volumes in computational intelligence spanning the areas of neural networks, connectionist systems, genetic algorithms, evolutionary computation, artificial intelligence, cellular automata, self-organizing systems, soft computing, fuzzy systems, and hybrid intelligent systems. Critical to both contributors and readers are the short publication time and world-wide distribution - this permits a rapid and broad dissemination of research results.   The purpose of the first ACIS International Symposium on Software and Network Engineering held on December 19-20, 2012 on the Seoul National University campus, Seoul, Korea is to bring together scientist, engineers, computer users, students to share their experiences and exchange new ideas, and research results about all aspects (theory, applications and tools) of software & network engineering, and to discuss the practical challenges encountered along the way and the solutions adopted to solve them   The symposium organizers selected the best 12 papers from those papers accepted for presentation at the symposium in order to publish them in this volume.  The papers were chosen based on review scores submitted by members of the program committee, and underwent further rigorous rounds of review.